Dinuclear uranium complexation and manipulation using robust tetraaryloxides. Issue 40 (26th August 2016) - Wells, Jordann A. L.; Seymour, Megan L.; Suvova, Markéta; Arnold, Polly L.
Abstract : Two lower-oxidation state uranium cations can be readily combined and controlled in a robust and derivatisable tetra-aryloxide ligand framework. These di-U III/IV systems are a new platform at which to use the multi-electron reductive capacity of the two actinide centres. Abstract : Two lower-oxidation state uranium cations can be readily combined in a robust, yet flexible and derivatisable, tetraaryloxide ligand framework, affording a new platform at which to use the multi-electron reductive capacity of the two actinide centres.